Postoperative Infection in Mesh Repair Hernias, Risk Factors and Management - Zainy , Hayder Mohammed Ali (South Asian Journal of Social Sciences and Humanities, 2025)
Background: A hernia occurs when a portion of the abdominal cavity's contents protrudes through a defect or weakness in the abdominal wall. Incisional hernias occur after surgery and are very common and challenging to repair. Mesh-related infections following incisional hernia repairs are significant complications with considerable morbidity. Aim of the Study: to describe our technique and management of patients with mesh related infection and offer a comprehensive review of surgical site infections following hernia surgery, focusing on the associated risk factors and management strategies. Methodology: a prospective interventional study that was conducted at Safeer Al-Imam Al Hussain Surgical Hospital, Imam Hussain Medical City, Zain Al-Abedin Surgical Hospital and Al-Kafeel Specialized Hospital / Karbalaa/ Iraq over 10 years (2014-2024). Forty patients with mesh infections post-incisional hernia repair were included. Data collected included demographic variables, risk factors, clinical variables, and treatment outcomes. Results: The study sample comprised 40 patients with a mean age of 52.3 years. Females comprised 32 (80%) of the patients. The infection resolved in 77.5% of patients with conservative treatment, while 22.5% required surgical mesh removal. Conclusions: Mesh-related infections after incisional hernia repair may occur as a complication after repair. Conservative treatment is often effective, but surgical removal is necessary for persistent infections. Addressing risk factors preoperatively may improve outcomes. Further research and refined techniques are needed to reduce infection rates and improve patient outcomes.
Keywords: Incisional hernia; Mesh-related infections; surgical site infection